MOBILITAS MIGRAN PEKERJA PEREMPUAN MUNTIGUNUNG, TIANYAR BARAT, KARANGASEM - Suwena, I Wayan (Jurnal Studi Jender SRIKANDI; Vol. 3, No. 1 Januari 2004, 2012)
In Muntigunung, the farmers? earning from agricultural sector is insufficient to fulfill of household need. And the limited of employment increase the social problems like poverty, beggar, child-waif and drop out of school, and also resident migration. The migrant women of Muntigunung earn for living in town because of their own willingness, invited by friends or relatives. Because of their low formal education, they work in informal sector. Besides increasing their earning, their job in informal sector also enable her to increase her skills and encourage her to compete in public sector. Kata kunci : migrasi, gepeng, sektor informal.
Keywords: MIGRASI